Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Profitabilitas Dengan Mediasi NPF Bank Umum Syariah - Zahra Latifah; Ade Ali Nurdin; Hazma Hazma (Indonesian Journal of Economics and Management, 2021)
This study aims to determine the influence of internal and external factors on profitability represented by Return On Assets (ROA) with the mediation of Non-Performing Financing in Islamic Commercial Banks 2014-2108. The internal factors used are CAR and FDR, then the external variables used are GDP and inflation. The method used in this research is path analysis with WarpPLS 6.0. From this research, it is found that the direct effect, namely CAR and GDP, has no effect on NPF. FDR has a significant negative effect on NPF, and the inflation variable has a negative effect on NPF. CAR has a significant positive effect on ROA. FDR, GDP and inflation have no effect on ROA, NPF has a significant negative effect on ROA. Meanwhile, the indirect effect, namely the NPF, does not mediate the effect of CAR and GDP on ROA. NPF mediates the effect of FDR and inflation on ROA.